Multimodal anti-Helicobacter pylori effects of Lactobacillus casei HY001: Evidence from in vitro and in vivo studies - Zhonghua Lv; Junqing Yu; Xueting Zhang; Lei Zhang; Chunlei Zhang; Xiaoxu Liu; Yu Chang; Hang Yin; Wei Wang; Haidan Zhao; Huicheng Li (PLoS ONE, 2026)
Helicobacter pylori ( H. pylori ) is a highly pathogenic microorganism that can cause various gastric diseases. Accumulating evidences have demonstrated probiotics’ potential in combating H. pylori infections. The aim of this study was to explore the effects and underlying mechanism of Lactobacillus casei ( L. casei ) HY001 against the gastric inflammation and gastric microbiota alteration induced by H. pylori infection. These results indicated that L. casei HY001 significantly inhibited the growth of H. pylori SS1, decreased urease activity, and exhibited strong co-aggregation properties with H. pylori SS1 in vitro experiments. Furthermore, L. casei HY001 was found to be capable of inhibiting the adhesion of H. pylori SS1 with AGS cells. Subsequently, Experiments in animals suggested L. casei HY001 alleviated gastric inflammation by inhibiting the expression of NF-κ B and reducing pro-inflammatory mediator levels (IL-8, TNF-α, IL-1β, and IL-6). Moreover, the gastric microbiota 16S rRNA gene sequencing analysis revealed that L. casei HY001 improved the structure of the gastric microbiota by modulating the abundance of Firmicutes , Bacteroidota and Proteobacteria. Meanwhile, the relative abundances of Rothia, Clostridium -sensu-stricto-1, Alistipe and Prevotellacea -UG-001 were significantly increased. In contrast, the abundances of Helicobacter , Turicibacter , unclassified – Muribaculaceae , unclassified- Oscillospiraceae and Lachnospiraceae -NK4A136-group were significantly reduced following HY001 intervention. These researches indicated that L. casei HY001 improved H. pylori SS1 induced gastric mucosal damage in mice, regulated immune factors, enhanced the reduced diversity of gastric Lachnospiraceae microbiota caused by H. pylori infection, and restored the stability of the microbial community structure.